HOW DO TRADE, INFLATION, EXCHANGE RATES, AND INFORMATION TECHNOLOGY INFLUENCE INTERNATIONAL TOURIST VISITS IN INDONESIA? - Jihan Nabila; Asma’ Munifatussa’idah (Airlangga Journal of Innovation Management, 2022)
This study aims to determine the short-term and long-term effects of trade, inflation, exchange rates, and information technology on international tourist visits in Indonesia. This study uses a quantitative approach within the Vector Error Correction Model (VECM) technique. The data used in this study are annual time series data of Indonesia trade, inflation, exchange rate and information technology on 1991-2019 period. The data used in this study were sourced from World Bank, International Monetary Fund (IMF), and Central Statistics Agency data. The results of the VECM research in the short term show that the variables of trade and information technology have a significant positive effect on international tourist visits. Meanwhile, inflation and exchange rates have a significant negative effect on international tourist visits. Then the results of VECM research in the long term show that variables of trade and information technology have a significant positive effect on international tourist visits. Meanwhile, inflation has a significant negative effect on international tourist visits. This study bring any literature contribution to future study that macroeconomics variables (trade, inflation) and information technology can influence the rise and fall of tourist visits to Indonesia. Practical contributions also brougt by this study as recommendations to increase international tourist visit in Indonesia for government and tourism stakeholder.